Lithium Niobate Single Crystals and Powders Reviewed—Part I - Farias, Rurik (2020)
A review of lithium niobate single crystals and polycrystals in the form of powders has been prepared. Both the classical and recent literature on this topic are revisited. It is composed of two parts with sections. The current part discusses the earliest developments in this field. It treats in detail the basic concepts, the crystal structure, some of the established indirect methods to determine the chemical composition, and the main mechanisms that lead to the manifestation of ferroelectricity. Emphasis has been put on the powdered version of this material: methods of synthesis, the accurate determination of its chemical composition, and its role in new and potential applications are discussed. Historical remarks can be found scattered throughout this contribution. Particularly, an old conception of the crystal structure thought as a derivative structure from one of higher symmetry by generalized distortion is here revived.